The Longitudinal Associations Between Outness and Health Outcomes Among Gay/Lesbian Versus Bisexual Emerging Adults. - Feinstein, Brian A.; Dyar, Christina; Li, Dennis H.; Whitton, Sarah W.; Newcomb, Michael E.; Mustanski, Brian (Archives of Sexual Behavior, 2019)
Sexual minorities are at increased risk for substance use and mental health problems. Although previous studies have examined the associations between outness and health outcomes, few have used longitudinal designs or examined differences across subgroups of sexual minorities. To address these gaps, the current study examined sexual orientation and gender as moderators of the longitudinal associations between outness and substance use (cigarettes, marijuana, illicit drugs, and alcohol) and mental health (depression and anxiety). Data were from a sample of 169 sexual minority emerging adults (98 women and 71 men) who provided self-report data at four times over 3.5 years. Results indicated that sexual orientation moderated the within-person associations between outness and changes in health. For bisexual individuals, being more out was associated with increases in marijuana use, illicit drug use, and depression. In contrast, for gay/lesbian individuals, being more out was associated with decreases in illicit drug use and it was not significantly associated with changes in marijuana use or depression. Additionally, outness was not significantly associated with changes in cigarette use, alcohol use, or anxiety for gay/lesbian or bisexual individuals, and gender did not moderate any of the associations. In sum, being more open about one's sexual orientation had negative consequences for bisexual individuals but not for gay/lesbian individuals. Professionals who work with sexual minorities need to be aware of the potential risks of being open about one's sexual orientation for bisexual individuals. Interventions are needed to facilitate disclosure decisions and to promote the health of sexual minorities.